Characterization of nano-crystalline Mg-Ni-Al hydrotalcite derived mixed oxides as hydrogen adsorbent - Salam, M.A. (2013)
A promising energy storage material containing magnesium, nickel and aluminum metals has been synthesized using conventional coprecipitation method. The physio-chemical properties, morphology and microstructure of hydrotalcite based mixed oxides (MNAM) have been characterized using ICP-MS, XRD, BET, FESEM and TEM techniques. The characterizations revealed that the adsorbent are highly dispersed, poly crystalline, homogenously distributed and interactive. Temperature programmed techniques have been used to explore the sorption capacities of mixed oxides. Nano-crystalline mesoporous and interactive reduced mixed oxides exhibit a 3.9 wt H2 adsorption capacity at ambient conditions. Temperature programmed desorption study predicted a desorption capacity of 1.9 wt H2. Different hydrogen adsorbed phases of magnesium and nickel have been characterized using HRTEM, Raman and FT-IR techniques. Â© 2013 Elsevier B.V. All rights reserved.